Vesicular stomatitis virus G glycoprotein pseudotyped retroviral vectors: concentration to very high titer and efficient gene transfer into mammalian and nonmammalian cells. - Burns, J C (1993)
The restricted host-cell range and low titer of retroviral vectors limit their use for stable gene transfer in eukaryotic cells. To overcome these limitations, we have produced murine leukemia virus-derived vectors in which the retroviral envelope glycoprotein has been completely replaced by the G glycoprotein of vesicular stomatitis virus. Such vectors can be concentrated by ultracentrifugation to titers > 10(9) colony-forming units/ml and can infect cells, such as hamster and fish cell lines, that are ordinarily resistant to infection with vectors containing the retroviral envelope protein. The ability to concentrate vesicular stomatitis virus G glycoprotein pseudotyped vectors will facilitate gene therapy model studies and other gene transfer experiments that require direct delivery of vectors in vivo. The availability of these pseudotyped vectors will also facilitate genetic studies in nonmammalian species, including the important zebrafish developmental system, through the efficient introduction and expression of foreign genes.